EXPERIMENTAL INVESTIGATION OF PARTIAL REPLACEMENT OF CEMENT BY VARIOUS PERCENTAGES OF SF AND FA IN CEMENT CONCRETE - Aishwarya, MR.; Suresh, R. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This project presents the results of research the use of various admixtures in concrete. The objective is effectively using the admixtures in concrete without affecting the quality of concrete. Experimental investigations were carried out to study the effect of use of SF (Silica Fume) as partial replacement of cement and Fly Ash as partial replacement of fine aggregate in concrete. Cement is partially replaced with various percentages (21%, 23%, 25%) of silica fume while fine aggregate is partially replaced with two percentages (15% and 20%).Data on the physical and chemical properties of the concrete constitutes the workability compressive strength, split tensile strength of concrete and admixtures mixed concrete are presented. To cast cubes of 150mm size. Silica Fume and fly ash replacement of cement concrete test specimens were cast. The strength development for various replacement of cement is compared to the strength of normal concrete at various ages and it was found that all the concrete mixes produce higher compressive strength than the conventional mix